Experimental and theoretical study on the corrosion inhibitor potential of quinazoline derivative for mild steel in hydrochloric acid solution - Fidelis Ebunta Abeng; Valentine Anadebe; Patience Yake Nkom; Enyinda Goodluck Kamalu; Kelechi J. Uwakwe (Journal of Electrochemical Science and Engineering, 2020)
Interaction of metal surfaces with organic molecules has a significant role in corrosion inhibition of metals and alloys. More clarification, from both experimental and computational view is needed in describing the application of inhibitors for protection of metal surfaces. In this study, the surface adsorption and corrosion inhibition behavior of metolazone, a quinazoline derivative, on mild steel in 0.02, 0.04, 0.06, and 0.08 M HCl solutions were investigated. Weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy techniques were used. The optimum inhibition efficiencies of 75, 82 and 83 % were found by these three techniques at the optimum inhibitor concentration of 500 mg/L and 303 K. Scanning electron microscopy (SEM) was used to confirm adsorption of quinazoline derivative on the surface of the mild steel. Computational simulations were additionally used to give insights into the interaction between quinazoline inhibitor and mild steel surface. Thermodynamic parameters of mild steel corrosion showed that quinazoline derivative functions as an effective anti-corrosive agent that slows down corrosion process. Potentiodynamic polarization results revealed a mixed-type inhibitor, while the result of the adsorption study suggests that adsorption of the inhibitor on the mild steel surface obeys the physical adsorption mechanism and follows Langmuir adsorption isotherm model.